2016
DOI: 10.1186/s12974-016-0657-9
|View full text |Cite
|
Sign up to set email alerts
|

SPARC expression by cerebral microvascular endothelial cells in vitro and its influence on blood-brain barrier properties

Abstract: BackgroundSPARC (secreted protein acidic and rich in cysteine) is a nonstructural, cell-matrix modulating protein involved in angiogenesis and endothelial barrier function, yet its potential role in cerebrovascular development, inflammation, and repair in the central nervous system (CNS) remains undetermined.MethodsThis study examines SPARC expression in cultured human cerebral microvascular endothelial cells (hCMEC/D3)—an in vitro model of the blood-brain barrier (BBB)—as they transition between proliferative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…Founding family member Secreted protein acidic and rich in Cysteine (SPARC), a matricellular protein bearing high structural homology to SPARCL‐1, has recently been reported to increase transendothelial permeability of the blood brain barrier (BBB) in vitro . SPARCL‐1 and SPARC exert antagonistic effects on cell adhesion and excitatory neuron synaptogenesis , but no function for SPARCL‐1 in BBB regulation has been ascribed so far.…”
Section: Discussionmentioning
confidence: 99%
“…Founding family member Secreted protein acidic and rich in Cysteine (SPARC), a matricellular protein bearing high structural homology to SPARCL‐1, has recently been reported to increase transendothelial permeability of the blood brain barrier (BBB) in vitro . SPARCL‐1 and SPARC exert antagonistic effects on cell adhesion and excitatory neuron synaptogenesis , but no function for SPARCL‐1 in BBB regulation has been ascribed so far.…”
Section: Discussionmentioning
confidence: 99%
“…Although rapid recanalization of the relevant artery and subsequent promotion of brain revascularization can successfully treat patients, reperfusion can increase the production of reactive oxygen species (ROS), inflammation and endoplasmic reticulum stress, leading to ischemia-reperfusion (I/R) injury, such as human brain microvascular endothelial cell (hBMEC) apoptosis ( 3 ). hBMECs, located between the blood and the brain parenchyma, are essential for normal neurological function and are responsible for transferring essential nutrients and removing potentially harmful toxins ( 4 ). I/R injury-induced hBMEC apoptosis impairs the therapeutic effect of relevant artery recanalization ( 5 – 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under physiological conditions, microvessels throughout most of the CNS possess a monolayer of endothelial cells connected with tight junctions and located between the blood and brain parenchyma, comprising the BBB together with adjacent astrocytes. 16 Numerous studies showed that neurovascular dysfunctions may contribute to the onset and progression of neurodegenerative diseases, such as AD by linking cerebrovascular changes and dysfunction. 17 Recently, the age-dependent deterioration of the BBB during normal aging in the human hippocampus was demonstrated.…”
Section: Introductionmentioning
confidence: 99%